Physical insights into alkaline overall water splitting with NiO microflowers electrodes with ultra-low amount of Pt catalyst. (19th September 2022) - Bruno, Luca; Battiato, Sergio; Scuderi, Mario; Priolo, Francesco; Terrasi, Antonio; Mirabella, Salvo
Abstract: Electrochemical water splitting represents a promising alternative to conventional carbon-based energy sources. The hydrogen evolution reaction (HER) is a key process, still if conducted in alkaline media, its kinetics is slow thus requiring high amount of Pt based catalysts. Extensive research has been focused on reducing Pt utilization by pursuing careful electrode investigation. Here, a low-cost chemical methodology is reported to obtain large amount of microflowers made of interconnected NiO nanowalls (20 nm thick) wisely decorated with ultralow amounts of Pt nanoparticles. These decorated microflowers, dispersed onto graphene paper by drop casting, build a high performance HER electrode exhibiting an overpotential of only 66 mV at current density of 10 mA cm −2 under alkaline conditions. Intrinsic activity of catalyst was evaluated by measuring the Tafel plot (as low as 82 mV/dec) and turnover frequencies (2.07 s −1 for a Pt loading of 11.2 μg cm −2 ). The effect of Pt decoration has been modelled through energy band bending supported by electrochemical analyses. A full cell for alkaline electrochemical water splitting has been built, composed of Pt decorated NiO microflowers as cathode and bare NiO microflowers as anode, showing a low potential of 1.57 V to afford a current density of 10 mA cm −2 and a good long-term stability. The reported results pave the way towards an extensive utilization of Ni based nanostructures with ultralow Pt content for efficient electrochemical water splitting. Highlights: Pt nanoparticles decoration of NiO microflowers. Effect of decoration on Hydrogen Evolution Reaction mechanism and on energy band modification of NiO. Overall water splitting with NiO and Pt–NiO electrodes in alkaline conditions.